PENDEKOMPOSISIAN CITRA DIGITAL DENGAN ALGORITMA DWT - Sriani Sriani; Triase Triase; Khairuna Khairuna (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2017)
The current large image storage capacity is increasingly important. This need, caused by the image to be stored more and more. Digital image processing in the field of image decomposition can be a solution to minimize memory needs in representing digital images. In this case the ratio in the decomposition process becomes the reference comparison between the decomposed image with the original image. In this research decomposition process using DWT algorithm. The image decomposition based discrete wavelet transform using the calculation system with the decomposition with the direction of the row and decomposition with the direction of the column. The decomposition process uses a leveling and subtraction formula by calculating the average value of two pairs of data. The results of this study indicate that the decomposition of digital images based on discrete wavelet transform is expected to be one useful algorithm in imaging technology for digital image decomposition. Keywords: digital image, decomposition, discrete wavelet transform